The Making of Resistance : Brazil's Landless Movement and Narrative Enactment - Lundström, Markus (Springer International Publishing : Imprint: Springer, 2017)
This Briefs advances a theoretical approach that recognizes social movements as contingent enterprises. It explores the endurance of social movements over time, by developing analytical tools to study how social movement heterogeneities are simultaneously acknowledged and articulated together, through collective narration and practices. With a unique empirical analysis of one particular narrative - the story of Brazil's Landless Movement - this Briefs portrays a narrative revisited and revised by movement participants, a story revived through enactment. This Briefs addresses the increasing academic audience seeking to study, and theorize, the multi-colored phenomena of resistance and social movements. .
Keywords: Social sciences.; Sociology.; Economic development.; Social change.; elektronické knihy; electronic books